Polymorphism in jasmonate signaling partially accounts for the variety of volatiles produced by Nicotiana attenuata plants in a native population - Schuman, Meredith Christine; Gaquerel, Emmanuel (The new phytologist, 2009)
Herbivore- and jasmonate-induced volatile organic compounds (VOCs), which mediate indirect defense, must provide reliable information for predators that frequently learn to associate their release with feeding herbivores. Yet little is known about variation of these cues within populations of native plants, on a scale encountered by predators. We examined variation in herbivore-elicited VOC emissions and patterns of herbivore-induced jasmonate signaling from accessions of Nicotiana attenuata co-occurring in a native population. VOC emissions elicited by herbivore oral secretions (OS) and by methyl jasmonate (MJ) were characterized using gas chromatography-mass spectrometry (GC-MS), high-resolution two-dimensional gas chromatography-time-of-flight mass spectrometry (GCxGC-ToF-MS) and micro-hydrolysis and micro-hydrogenation reactions. Accessions varied in emissions of abundant (trans-α-bergamotene, α-duprezianene, trans-β-ocimene, and cis-3-hexenol) and total detectable VOCs, as well as the accumulation of jasmonates, the jasmonate antagonist salicylic acid (SA), abscisic acid (ABA) and jasmonate signaling-related transcripts after OS elicitation. Yet MJ treatment exacerbated differences in VOC emission, suggesting that much variation in VOC emission is caused by processes downstream of jasmonate signaling. Co-occurring N. attenuata plants emit different VOCs following simulated herbivore elicitation as a result in part of differences in jasmonate production and responsiveness, which could reduce the effectiveness of induced indirect defense.